The Concise Oxford English- Arabic Dictionary of Current Usage - N. S. Doniach; Safa Khulusi; N. Shamaa; W. K. Davin (UK Oxford University Press, 1982)
This dictionary is designed for both the English speaker learning Arabic and the Arabic speaker learning English. It records the different levels of usage found in newspapers, radio, television, and films, providing major Arabic dialectal equivalents for familiar, colloquial, and slang words. The dictionary includes: nearly 40,000 entries providing English headwords with multiple meanings and their nearest Arabic equivalent, phonetic equivalents for headwords, phrases illustrating unexpected and alien idioms, and explanations of headwords denoting concepts new to the Arab world, and vowels and diacritics included in the Arabic text, irregular plurals of nouns, and simple verb conjugations in the imperfect tense
Abridged ed. of: The Oxford English-Arabic dictionary of current usage / edited by N.S. Doniach. 1972
Keywords: Languages (3GddZGJs; General -- Dictionaries -- Arabic; English language